An Industrial Systems Approach to Utilizing Sweet Potatoes as a Nutritious Local Food for Stunting Prevention - Anita, Anita; Wahyudi, Rakhmad; Rakhmawati, Ismi Yayuk; Ahmad, Nuril (Borneo Novelty Publishing, 2026)
Stunting is a chronic nutritional problem that has a significant impact on the quality of human resources in Indonesia, both in the short term through increased risk of morbidity and mortality, and in the long term through decreased intellectual capacity that has the potential to cause a lost generation. Therefore, stunting prevention is a national priority that requires a systematic approach, including optimizing the use of local resources in a nutritious food supply system. This study aims to compile a scientific review of the potential of sweet potatoes as a local food ingredient for stunting prevention from an industrial systems perspective. The method used is a literature review with a descriptive qualitative approach to various relevant scientific sources. The study results indicate that sweet potatoes (Ipomoea batatas L.) have strategic value as a raw material in the nutritious food industry value chain due to their nutritional content, including carbohydrates, protein, fat, fiber, vitamin A, and antioxidants, which support the fulfillment of children's nutritional needs. Through an industrial systems approach, sweet potatoes can be developed into various value-added food products such as purees, instant porridge, cookies, sponge cakes, and nuggets that not only increase public access to nutritious food but also strengthen the sustainability of the healthy food supply system in an effort to accelerate stunting reduction.